2019
DOI: 10.1186/s13036-019-0195-y
|View full text |Cite
|
Sign up to set email alerts
|

Modified substrate specificity of a methyltransferase domain by protein insertion into an adenylation domain of the bassianolide synthetase

Abstract: Background Creating designer molecules using a combination of select domains from polyketide synthases and/or nonribosomal peptide synthetases (NRPS) continues to be a synthetic goal. However, an incomplete understanding of how protein-protein interactions and dynamics affect each of the domain functions stands as a major obstacle in the field. Of particular interest is understanding the basis for a class of methyltransferase domains (MT) that are found embedded within the adenylation domain (A) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…A series of radiometric and MS/MS assays demonstrated that the A, M s , and M b domains of ColG­(AM s M b A) function as we had hypothesized. The A domain specifically adenylated l -Ser, the M s domain (closest to the N-terminus of the ColG­(AM s M b A) enzyme) methylated the oxygen on the side chain of l -Ser and not the sulfur of l -Cys, and the M b domain (closest to the C-terminus of the ColG­(AM s M b A) enzyme) mono/dimethylated the nitrogen on the backbone of l -Ser as well as l -Cys and its methylated derivatives, as consistent with the relaxed specificity observed in other backbone M domains. ,, …”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…A series of radiometric and MS/MS assays demonstrated that the A, M s , and M b domains of ColG­(AM s M b A) function as we had hypothesized. The A domain specifically adenylated l -Ser, the M s domain (closest to the N-terminus of the ColG­(AM s M b A) enzyme) methylated the oxygen on the side chain of l -Ser and not the sulfur of l -Cys, and the M b domain (closest to the C-terminus of the ColG­(AM s M b A) enzyme) mono/dimethylated the nitrogen on the backbone of l -Ser as well as l -Cys and its methylated derivatives, as consistent with the relaxed specificity observed in other backbone M domains. ,, …”
Section: Resultssupporting
confidence: 63%
“…The A domain specifically adenylated L-Ser, the M s domain (closest to the N-terminus of the ColG(AM s M b A) enzyme) methylated the oxygen on the side chain of L-Ser and not the sulfur of L-Cys, and the M b domain (closest to the C-terminus of the ColG(AM s M b A) enzyme) mono/dimethylated the nitrogen on the backbone of L-Ser as well as L-Cys and its methylated derivatives, as consistent with the relaxed specificity observed in other backbone M domains. 14,33,34 Nature continuously surprises us with new ways to introduce diversity in NPs and inspires us to create new ways to hopefully, in the future, produce biologically active "unnatural" natural products. The insights gained in this study open a variety of avenues for enzyme engineering and combinatorial biosynthesis studies for eventual drug discovery.…”
Section: Acs Chemical Biologymentioning
confidence: 99%
“…This domain is usually integrated inside of A domain such as MT domain of cyclosporine A NRPS (Velkov et al, 2011). A recent engineering example of the MT domain in module 2 of bassianolide synthetase showed that the deletion of this domain generated the N-desmethylbassianolide without affecting the enzyme assembly lines (Xu et al, 2019). In another study, O-methylating MT domain was inserted between the A subdomains, resulting in the incorporation of O or N-methylated serine (Lundy et al, 2018).…”
Section: Processing and Offloading Domain Engineering Of Nrpsmentioning
confidence: 99%
“…However, from the sequence of a BGC it is difficult to predict whether a separately encoded enzyme will act on an acyl substrate before assembly-line synthesis, on a PCP-tethered intermediate of NRPS assembly-line synthesis, or on a small molecule after release from the NRPS. The natures of these possible substrates are quite different, and an enzyme will act on only one of these species 24 , 32 .…”
Section: Introductionmentioning
confidence: 99%